Abscesses and cysts of Bartholin’s gland - contemporary problems of active women - Panuciak, Kinga; Mastalerczyk, Angelika; Nowicka, Emilia; Makowska, Karolina; Obel, Michał; Lejman, Jan; Czyżak, Kamila; Wiśniewski, Wiktor (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Bartholin’s glands are paired structures, playing a significant role in lubricating the vagina through the production of mucus. They are physiologically undetectable, but when their ducts are clogged, the accumulating secretion can lead to various pathologies. The most common are cysts and abscesses, the symptomatic conditions of which are the causes of nearly 2% of gynecological visits annually. Statistically, they most frequently occur in women of childbearing age, however, young age is not a rule. The aim of the study is to summarize the state of knowledge about Bartholin’s gland cysts and abscesses, with an indication of the currently used therapies. State of knowledge: In some cases, the course of these pathologies can be asymptomatic, however, the rest of the patients may experience unpleasant symptoms and require treatment. During diagnostics, it is important to carefully collect an interview and conduct a physical examination, because in most cases on this basis it is possible to make an accurate diagnosis. However, in case of doubt, imaging tests can also be used. There may be times when patients with asymptomatic cysts may not require treatment. Nevertheless, choosing the right therapy is sometimes challenging for the clinician due to the potential risk of symptoms recurring. Conclusion: Although there are many different treatments available, the most commonly used appears to be marsupialization or incision and drainage with Word catheter placement. Additionally, an increasing number of articles devoted to the use of the CO2 laser can also be observed, but even it has its drawbacks. For this reason, there is still a need for further research into new methods of treatment that would ensure both good results and high comfort for the patients.